Geo-electrical Investigations for Shallow Ground Water at IARI Farm, New Delhi - Raut, Sushil; Chandrasekharan, H; Sarma, K S.Sundara; Singh, A; Yadav, B R (Annals of Arid Zone, 2016)
Vertical Electrical Soundings (VES) adopting Schlumberger configuration and profiling by Wenner configuration, were carried out at 16 locations and along two traverses, to assess the ground water potential zones and their continuity in a micro-watershed at JAR! Farm. New Delhi. Five geoelectric layers werc identified within a depth of about 40m below ground level. VES data from two points were compared with the bore hole litholog obtained from secondary data. Using the resistivity fence diagram and thc geometry of the aquifer zone, approximate quantity of ground water under phreatic condition was computed. Chcmical analyscs of ground water samples indicatcd medium to slightly higher salinity and low alkali hazard. which could be grouped as C3St under USDA classification of irrigation watcr quality.